The effect of milking methods on milk production and its components and the relationship between milk components and biochemical characteristics of blood in Awassi sheep - Al- Hubaety, Arif K. H.; Al- Juwari, Muthanna F. A. (Journal of agricultural, environmental and veterinary sciences, 2021)
The study included 72 Awassi ewes aged 5 years. The current study aimed to the effect of three milking methods (hand milking, oxytocin injection, weight- suckle- weight (WSW)) on milk production and its components, and the relationship between the milk production and components with biochemical blood component. The lowest significant production was (p≤0.05) for daily milk for the hand milking group, the WSW group was significantly superior (p≤0.05) than the hand milking group in producing milk before weaning. The shortest milk season for the oxytocin injection group was significant. Significant differences (p≤0.05) were observed in fat percentage in favor of the WSW group. There was a negative and significant correlation between milk production and the percentage of fat, protein, lactose and solids non- fat, and it was- 0.340,- 0.077,- 0.133, and- 0.091, respectively. A significant decrease (p≤0.05) was observed in the level of total protein, cholesterol, and blood glucose at the first month after birth, while the differences were not significant between the remaining months. There was a negative and significant correlation between the percentage of lactose, and solids non- fat with blood glucose, which reached- 0.429 and- 0.420 at the first month, and positive and highly significant (p≤0.01) between the fat percentage and blood protein in the second month amounted to 0.493, while the correlation was negative and significant between blood protein and milk production at the third month- 0.375 and the correlation between blood protein, lactose percentage and solids non- fat at the fourth month, were- 0.656 and- 0.550, respectively.
Keywords: milking methods; milk production and its components; biochemical characteristics of blood; Awassi sheep